A new species of Noticastrum DC. (Compositae, Astereae) from northern Peru - Montoya Quino, Juan; Herbario CPUN, Universidad Nacional de Cajamarca (2023)
The new species Noticastrum sanchezvegae for the paramo of northern Peru, from the departmentof Cajamarca, is described and illustrated. For this purpose, the differential characters with respectto N. macbridei Cuatrec. from central Peru are indicated, and a new key is given for the 21 speciesdescribed in South America. N. sanchezvegae is distinguished from the rest of the species by its denseindumentum of glanduliferous and non-glanduliferous trichomes that give the plants a woollyappearance, and the small size of flowers and achenes.